Russification – surzhik – vulgarization in the communicative discourse of the Ukrainian multicultural space (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article highlights the question of Russification of the Ukrainian people by the repressive apparatus of the tsarist Russia and the ideologists of Marxism-Leninism of the USSR. Attention is attracted to strategic methods of assimilation of Ukrainians by the prohibition to study in their native language (formal, informal circulars in the times of tsarism and the Soviet power), the persecution of nationally conscious Ukrainian intelligentsia in the education system, culture, religion, publishing activities, as well as to methods of combating “Ukrainian separatists” and methods of punishment for disobedience of compliance the existing power’s laws. Ubiquitous “surzhyk” has been inherited as the result of long assimilation of the Ukrainian ethnos and the power structures’ invertebrate attitude in sovereign Ukraine. It continues to function, foreign borrowings have intensified. There are language shifters, grammatical and stylistic flaws and obscene language are present not only in everyday speech, but in the media, artistic and scientific literature. Widespread calques from the Russian language those language units which are in the Ukrainian language have their equivalents in the literature, lexicon and terminology.Leading linguists, cultural workers, writers, teachers of secondary and higher educational establishments of Ukraine constantly warn about the threat of linguistic blockage “surzhyk”, foreign languages, producing language freaks, the deformation of Ukrainian names. However the reaction to such cautions of public officials remains very slow. Moreover, finally, we have the new Law on Education, but the shameful Law by Kivalov-Kolesnichenko on granting of the state status of Russian language adopted by the Verkhovna Rada of Ukraine has been not cancelled yet. Such entertainment-bilingually Shtepsel-Tarapunkin variant of language is thoroughly improved by modern Ukrainian mass media, fostered by Soviet ideologists. It is the fertile ground for “surzhyk” and the culture of Ukrainian broadcasting decline. And that is why there is an urgent need to eradicate this negative phenomenon by such legal status, which would be carefully guarded the purity of the Ukrainian language and had legal sanctions to protect it from any attack.
Keywords: russification; assimilation; surzhyk; foreign borrowings; loan translation; media; culture of speech